Late-Holocene floodplain development, land-use, and hydroclimate–flood relationships on the lower Ohio River, US. (December 2019) - Bird, Broxton W; Barr, Robert C; Commerford, Julie; Gilhooly, William P; Wilson, Jeremy J; Finney, Bruce; McLauchlan, Kendra; Monaghan, G William
Floodplain development, land-use, and flooding on the lower Ohio River are investigated with a 3100-year-long sediment archive from Avery Lake, a swale lake on the Black Bottom floodplain in southern Illinois, US. In all, 12 radiocarbon dates show that Avery Lake formed at 1130 BCE (3100 cal. yr BP), almost 3000 years later than previously thought, indicating that the Black Bottom floodplain is younger and more dynamic than previously estimated. Three subsequent periods of extensive land clearance were identified by changes in pollen composition, corresponding to Native American occupations before 1500 CE and the current Euro-American occupation beginning in the 18th century. Sedimentation rates prior to 1820 CE changed independently of land clearance events, suggesting natural as opposed to land-use controls. Comparison with high-resolution paleoclimate data from Martin Lake, IN, indicates that lower Ohio River flooding was frequent when cold-season precipitation originating from the Pacific/Arctic predominated when atmospheric circulation resembled positive Pacific North American (PNA) conditions and the Pacific Decadal Oscillation (PDO) was in a positive mean state (1130 BCE to 350 CE and 1150–1820 CE). Conversely, Ohio River flooding was less frequent when warm-season precipitation from the Gulf of Mexico prevailed during negative PDO- and PNA-like mean states (350 and 1150 CE). This flood dynamic appears to have been fundamentally altered after 1820 CE. We suggest that extensive land clearance in the Ohio River watershed increased runoff and landscape erosion by reducing interception, infiltration, and evapotranspiration, thereby increasing flooding despite a shift to negative PDO- and PNA-like mean states. Predicted increases in average precipitation and extreme rainfall events across the mid-continental US are likely to perpetuate current trends toward more frequent flood events, because anthropogenic modifications have made the landscape less resilient to changing hydroclimatic conditions.